2017
DOI: 10.14814/phy2.13397
|View full text |Cite
|
Sign up to set email alerts
|

Acute heat stress activated inflammatory signaling in porcine oxidative skeletal muscle

Abstract: Despite well‐studied clinical manifestations, intracellular mechanisms of prolonged hyperthermic injury remain unclear, especially in skeletal muscle. Given muscle's large potential to impact systemic inflammation and metabolism, the response of muscle cells to heat‐mediated injury warrants further investigation. We have previously reported increased activation of NF‐κB signaling and increased NF‐κB and AP‐1‐driven transcripts in oxidative skeletal muscle following 12 h of heat stress. The purpose of this inve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
25
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 41 publications
(26 citation statements)
references
References 40 publications
1
25
0
Order By: Relevance
“…We have previously seen that 15 min of recovery was enough for HSF1 hyperphosphorylation to return to thermoneutral (TN) levels (data not shown). An in vivo study reported no changes in skeletal muscle Hsp70 expression when pigs were exposed to 2, 4, or 6 h of HS (Ganesan et al, 2017b). Whereas we observed a significant duration-dependent elevation of Hsp70 during recovery.…”
Section: Discussionmentioning
confidence: 99%
“…We have previously seen that 15 min of recovery was enough for HSF1 hyperphosphorylation to return to thermoneutral (TN) levels (data not shown). An in vivo study reported no changes in skeletal muscle Hsp70 expression when pigs were exposed to 2, 4, or 6 h of HS (Ganesan et al, 2017b). Whereas we observed a significant duration-dependent elevation of Hsp70 during recovery.…”
Section: Discussionmentioning
confidence: 99%
“…Heat stress is known to cause increased muscle catabolism (Pearce et al, 2013;Cruzen et al, 2017;Ganesan et al, 2017). The protein catabolism indicator, BUN, was elevated by both HS and AHS treatments.…”
Section: Discussionmentioning
confidence: 99%
“…There are inconsistent in the effects of heat stress on NF‐κB expression. Heat stress inhibited the NF‐κB expression (Ohno et al, ) or activated the NF‐κB expression (Ganesan et al, ), which suggested that the importance of heat‐stressed property in the modulation on the NF‐κB expression. Our results showed that heat stress increased the NF‐κB expression, and excessive NF‐κB activation contributes to intestinal inflammation (De Plaen et al, ).…”
Section: Discussionmentioning
confidence: 99%